Method for in-situ preparation of biomass-based geopolymer composite microspheres

By preparing biomass-based geological polymer composite microspheres in situ, the problem of difficulty in effectively dealing with complex industrial wastewater in the existing technology is solved, and efficient adsorption of heavy metals and organic pollutants in printing and dyeing wastewater and electroplating wastewater is achieved, and the materials are environmentally friendly and low-cost.

CN119822700APending Publication Date: 2025-04-15GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510043102.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat complex industrial wastewater, such as printing and dyeing wastewater and electroplating wastewater, especially because these wastewaters contain a variety of heavy metal ions and complex organic pollutants, making it difficult to deal with it.

Method used

By preparing biomass-based geological polymer composite microspheres in situ, using agricultural waste and industrial waste as raw materials, combining alkaline exciters and ammonia water treatment, forming composite microsphere materials with high adsorption capacity. The method includes mixing biomass powder, aluminosilicate raw material and alkaline exciter, dripping into silicone oil and stirring, followed by oven maintenance, vacuum suction filtration, immersion of ammonia water and high temperature insulation, and finally obtaining biomass-based geological polymer composite microspheres by washing and drying pure water.

Benefits of technology

The prepared biomass-based geological polymer composite microspheres show good adsorption function, and have high-efficiency adsorption effect on various contaminated aqueous solutions. They can effectively treat heavy metal ions and organic pollutants in printing and dyeing wastewater and electroplating wastewater. The material itself is green and environmentally friendly and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822700A_ABST
    Figure CN119822700A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ preparation of biomass-based geopolymer composite microspheres, and belongs to the field of geopolymer composite material preparation. The preparation method comprises the following steps: uniformly mixing biomass powder, an aluminosilicate raw material and an alkaline activator to obtain slurry, dropwise adding the slurry into silicone oil under a stirring condition, continuously stirring for 10-15 minutes after titration is completed, transferring into a drying oven for curing, carrying out vacuum suction filtration, soaking the obtained solid in ammonia water, carrying out heat preservation at 350-500 DEG C for 3-5 hours in a high-purity nitrogen atmosphere, and cooling to room temperature to obtain the high-purity aluminosilicate composite material. After cooling, washing to be neutral by using pure water, and drying to obtain the biomass-based geopolymer composite microspheres. The novel green, environment-friendly and low-cost composite microsphere adsorption material prepared by the method has a better adsorption function on various pollutants in an aqueous solution, is an adsorbent with excellent comprehensive performance, and can be used for treating industrial wastewater such as printing and dyeing wastewater and electroplating wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geopolymer composite material preparation, and in particular to a method for in-situ preparation of biomass-based geopolymer composite microspheres. Background Art

[0002] Geopolymers, also known as inorganic polymer materials, are amorphous three-dimensional network gels generated by the condensation reaction of aluminum silicate minerals under the action of an activator. Their raw materials come from a wide range of sources, including kaolin, fly ash, slag, silica fume, etc. This type of material has the advantages of high strength, good weather resistance, and low carbon production process. Its application and development is an important direction for the future development of inorganic gelling materials.

[0003] Biomass includes all plants, microorganisms, and animals that feed on plants and microorganisms and their waste products, such as crops, crop waste, wood, wood waste, straw, trees and other lignocellulose in the agricultural and forestry production process other than grain and fruit, and livestock manure and waste in the animal husbandry production process. Biomass undergoes thermochemical conversion under oxygen-limited or oxygen-free conditions to produce a carbon-rich solid material called biochar. In recent years, research on biochar has mainly focused on the following aspects: (1) Biochar as a reinforcing filler to replace other inorganic fillers; (2) Biochar-polymer composites are explored as a sustainable alternative to traditional carbonaceous fillers for the development of polymer-based composites; (3) The application of biochar and its composites in pollution control; (4) Research on biomass composites as thermal insulation materials.

[0004] Agricultural waste and industrial waste are the main bulk solid wastes that are currently waiting to be developed and utilized. At present, there are studies on the composite of biochar obtained by carbonizing agricultural solid waste biomass with industrial solid waste and waste residue, but there are few studies on the in-situ composite of biomass and geopolymers, and there is no public or report on the composite of the two into microsphere materials.

[0005] Printing and dyeing wastewater and electroplating wastewater are both industrial wastewaters with large discharge volumes and difficult to treat. Printing and dyeing wastewater has high chromaticity and complex composition. In addition to residual dyes, it also contains heavy metals such as Cd and Pb, which are highly toxic. Due to the complex composition of printing and dyeing wastewater and the difficulty in treatment, printing and dyeing wastewater treatment has been facing various technical difficulties for many years. The composition of electroplating wastewater is complex, and organic pollutants include surfactants, organic acids, organic solvents and dyes. In addition, electroplating wastewater also contains a large amount of heavy metal ions, such as chromium, nickel, lead, copper, cobalt, etc. These heavy metal ions are highly toxic and difficult to degrade, which are extremely harmful to water bodies and the ecological environment. Summary of the invention

[0006] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art and to provide a method for in situ preparation of biomass-based geopolymer composite microspheres, which utilizes agricultural waste and industrial waste as raw materials to prepare a new type of green, environmentally friendly, low-cost composite microsphere adsorption material, which has good adsorption function for a variety of simulated polluted aqueous solutions and is an adsorbent with excellent comprehensive performance, and can be used in the treatment of industrial wastewater such as printing and dyeing wastewater and electroplating wastewater.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for in-situ preparation of biomass-based geopolymer composite microspheres comprises the following steps: uniformly mixing biomass powder, aluminosilicate raw material and alkaline activator to obtain slurry, dripping the slurry into 70-90°C silicone oil under stirring, continuously stirring for 10-15min after the titration is completed, then transferring to a 70-90°C oven for curing for 8-12h, then performing vacuum filtration, soaking the obtained solid in ammonia water for 5-8h, then keeping the temperature at 350-500°C for 3-5h in a nitrogen atmosphere, washing with pure water to neutrality after cooling, and drying to obtain biomass-based geopolymer composite microspheres.

[0009] Furthermore, the concentration of the ammonia water is 5-10 mol / L.

[0010] Furthermore, the biomass powder is any one or any combination of eucalyptus wood powder, bagasse powder, and wheat straw powder.

[0011] Furthermore, the aluminosilicate raw material is any one of metakaolin and slag, or a combination of the two.

[0012] Furthermore, the alkaline activator is 1.0 modulus water glass or 10-20 mol / L NaOH solution.

[0013] Furthermore, the amount of the biomass powder added is 5-7g, the amount of the aluminosilicate raw material added is 25-30g, and the amount of the alkaline activator added is 25-50g.

[0014] Furthermore, the added amount of the biomass powder is 15-25% of the total weight of the biomass powder and the aluminosilicate raw material.

[0015] The present invention also provides application of the biomass-based geopolymer composite microspheres prepared by the above method in industrial wastewater treatment.

[0016] Furthermore, the industrial wastewater is printing and dyeing wastewater or electroplating wastewater.

[0017] Furthermore, the application is to add the biomass-based geopolymer composite microspheres into industrial wastewater for stirring or shaking, and the added concentration of the biomass-based geopolymer composite microspheres in the industrial wastewater is 0.5-1.5 g / L.

[0018] The beneficial effects of the present invention are as follows:

[0019] The present invention prepares geopolymers by suspended solidification loads of agricultural waste such as eucalyptus branches, wheat straw, bagasse and industrial raw materials / solid waste such as metakaolin and slag, and then prepares the two into composite materials that can treat complex pollutants - biomass-based polymer composite microspheres through in-situ activation, realizing the environmental protection development concepts of "treating waste with waste", "resource reuse of agricultural waste" and "improving the utilization efficiency of bulk solid waste resources".

[0020] The present invention composites the precursor of biochar with geopolymer, uses an alkaline solution for secondary activation after the microspheres are prepared, and can in-situ carbonize the biomass powder loaded on the surface of the geopolymer during the calcination stage, further expanding the pore structure generated on the surface of the biomass powder after carbonization, while ensuring that the material can be applied to the fixed bed, and enhancing the adsorption capacity of the geopolymer itself. The biomass-based geopolymer composite microspheres of the present invention can be effectively used in the treatment of industrial wastewater such as printing and dyeing wastewater and electroplating wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The SEM images of biomass-based geopolymer composite microspheres of Examples 1-4, in which a and b are eucalyptus-metakaolin-based composite microspheres of Example 1; c and d are bagasse-slag-based composite microspheres of Example 3; e and f are eucalyptus-slag-based composite microspheres of Example 2; g and h of Example 4 are wheat straw-slag-based composite microspheres;

[0022] Figure 2 It is a comparison diagram of the adsorption effect of biomass-based geopolymer composite microspheres of Examples 1-4 on CV and CR;

[0023] Figure 3 This is a comparison chart of the adsorption effects of biomass-based geopolymer composite microspheres of Examples 1-4 on Cd and Pb;

[0024] Figure 4 It is a comparison chart of the adsorption effect of biochar or geopolymer microspheres of comparative examples 1-5 on CV and CR;

[0025] Figure 5 It is a comparison chart of the adsorption effect of biochar or geopolymer microspheres of comparative examples 1-5 on Cd and Pb;

[0026] Figure 6 , Figure 7This is a comparison chart of the treatment effects of biochar or geopolymer microspheres of Example 2, Example 3, Comparative Example 2, Comparative Example 3, and Comparative Example 6 on simulated electroplating wastewater. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0028] The raw materials used in the following examples mainly include industrial raw materials / solid waste metakaolin, slag, agricultural solid waste eucalyptus branches, wheat straw, and sugarcane bagasse. All of the above materials are made into powder and have passed through a 200-mesh sieve.

[0029] Example 1

[0030] Adjust the water glass modulus to 1.0 with sodium hydroxide and set aside after cooling to room temperature. Biochar-geopolymer composite microspheres were prepared by suspension solidification method, and the process was as follows: 6.586g eucalyptus powder and 26.344g metakaolin were added into a beaker, wherein the amount of eucalyptus powder added was 20% of the total weight of the eucalyptus powder and metakaolin, 50g 1.0 modulus water glass and 20.75g pure water were added, and a disperser was used to stir at a high speed of 1200r / min for 10min, and the obtained slurry was transferred to a dropping funnel, and the slurry was dripped into 80°C silicone oil under stirring. After dripping, the slurry was transferred to an oven at 80°C after continuous stirring for 10min, and vacuum filtered after curing for 12h. The filtered solid was added into 6mol / L ammonia water and immersed for 5h and then filtered. The obtained solid was placed in a porcelain boat, and kept at 400°C for 4h in a nitrogen atmosphere in a tubular furnace. After cooling, the sample was washed with pure water until neutral, and dried to obtain biomass-based geopolymer composite microspheres, i.e., eucalyptus-metakaolin-based composite microspheres, numbered AMK.

[0031] Example 2

[0032] NaOH and water are used to prepare a 12 mol / L NaOH alkaline solution, which is cooled to room temperature and set aside for use. The biochar-geopolymer composite microspheres are prepared by the suspension solidification method. The process is as follows: 6 g of eucalyptus wood powder and 24 g of slag are added to a beaker, and the prepared 29.22 g of alkaline solution is added. A disperser is used to stir at a high speed of 1200 r / min for 10 min, and the obtained slurry is transferred to a dropping funnel. The slurry is dripped into 80°C silicone oil under stirring conditions. After dripping, it is transferred to an oven at 80°C after continuous stirring for 10 min. After curing for 8 h, vacuum filtration is performed. The filtered solid is added to 8 mol / L ammonia water and immersed for 7 h and then filtered. The obtained solid is placed in a porcelain boat and kept at 400°C for 4 h in a tubular furnace under a nitrogen atmosphere. After cooling, the sample is washed with pure water until neutral. After drying, biomass-based geopolymer composite microspheres, i.e., eucalyptus-slag-based composite microspheres, are obtained, which are numbered AGM.

[0033] Example 3

[0034] NaOH and water were used to prepare a 15 mol / L alkaline solution, which was cooled to room temperature and then used for standby. The biochar-geopolymer composite microspheres were prepared by the suspension solidification method. The process was as follows: 6 g of bagasse powder and 24 g of slag were added to a beaker, and 45 g of the prepared alkaline solution was added. The disperser was used to stir at a high speed of 1200 r / min for 10 min, and the obtained slurry was transferred to a dropping funnel. The slurry was dripped into 80°C silicone oil under stirring. After dripping, the slurry was transferred to an oven at 80°C after continuous stirring for 10 min. After curing for 8 h, vacuum filtration was performed. The filtered solid was added to 10 mol / L ammonia water and immersed for 5 h and then filtered. The obtained solid was placed in a porcelain boat and kept at 400°C for 4 h in a tubular furnace under a nitrogen atmosphere. After cooling, the sample was washed with pure water until neutral. After drying, biomass-based geopolymer composite microspheres, i.e., bagasse-slag-based composite microspheres, were obtained, which were numbered ZGM.

[0035] Example 4

[0036] NaOH and water were used to prepare a 17 mol / L alkaline solution, which was cooled to room temperature and then used for standby. The biochar-geopolymer composite microspheres were prepared by the suspension solidification method. The process was as follows: 6 g wheat straw powder and 24 g slag were added to a beaker, and 40 g of the prepared alkaline solution was added. The disperser was used for high-speed stirring for 10 min, and the obtained slurry was transferred to a dropping funnel. The slurry was dripped into 80°C silicone oil under stirring conditions. After dripping, it was continuously stirred at 1200 r / min for 10 min and then transferred to an oven at 80°C. After curing for 8 h, vacuum filtration was performed. The filtered solid was added to 6 mol / L ammonia water and immersed for 8 h and then filtered. The obtained solid was placed in a porcelain boat and kept at 400°C for 4 h in a tubular furnace under a nitrogen atmosphere. After cooling, the sample was washed with pure water until neutral. After drying, biomass-based geopolymer composite microspheres, i.e. wheat straw-slag-based composite microspheres, were obtained, which were numbered XGM.

[0037] like Figure 1 As shown in the figure, the SEM electron microscope photos show the surface microstructure of four biomass-doped geopolymer microsphere adsorbents. Figure 1 As shown in (a), (c), (e), and (g), the sphericity of the composite microspheres is not greatly affected after the biomass is doped. Part of the biomass is solidified on the surface of the microspheres, and part of it is wrapped in the geopolymer. The addition of biomass does not interfere with the structure and texture of the geopolymer, while expanding the pore structure of the geopolymer itself and providing more adsorption sites for adsorption. Figure 1 As shown in (b), (d), (f), and (h), while the biomass is solidified, it is tightly combined with the tiny nanoparticles in the industrial solid waste. The surface of the adsorbent not only shows the loose and porous biomass after carbonization, but also has the fine pores on the surface of the geopolymer. During the balling process of the geopolymer microsphere composite material, the strong alkalinity will cause the biomass itself to undergo preliminary modification, weaken the hydrogen bonding inside the fiber in the biomass, cause the cellulose to swell, dissolve the hemicellulose and part of the lignin, and maximize the surface area of ​​the adsorbent material after balling. After balling, the biomass is further activated during the modification process by being impregnated with an alkaline solution. Under the protection of high-purity nitrogen, the high-temperature in-situ calcination at 400℃ for 4h is carried out. The surface biomass of the composite microspheres will undergo an in-situ carbonization process at high temperature. During the carbonization process, the biomass will again increase the surface pore size of the composite microspheres, so that there are a large number of adsorption sites in the pores. The spherical adsorbent formed in this way can be successfully used in fixed bed adsorption, which better solves the problem of inconvenient recovery of traditional adsorption materials after application.

[0038] Application Examples

[0039] The biomass-based geopolymer composite microspheres prepared in Examples 1-4 were used as adsorbents to perform adsorption experiments on dye crystal violet (CV), Congo red (CR) and heavy metals Cd and Pb. The specific operations were as follows:

[0040] Weigh 1g of CV and CR powders and appropriate amounts of Cd and Pb nitrate particles and place them in a clean beaker, add deionized water and stir, ultrasonicate for 30 minutes to fully dissolve them, make up to volume with a 1000mL volumetric flask, shake evenly to obtain a 1000mg / L pollutant mother liquor; take the above pollutant mother liquors and dilute them to 100mg / L CV, 100mg / L CR, 200mg / L Cd ions, and 300mg / L Pb ions, respectively, to obtain the prepared pollutant solutions.

[0041] Measure 100 mL of the prepared pollutant solution into a reagent bottle, add 0.075 g of adsorbent, and shake at 250 r / min in an air shaker at 25°C for 24 hours. After sampling, use a UV-visible spectrophotometer and an atomic absorption spectrophotometer to test the ion concentration. The adsorption amount of formula (1) and the removal rate of formula (2) are used to characterize the adsorption effect of the composite microspheres:

[0042]

[0043] Where Q is the adsorption capacity of the adsorbent, mg / g; R is the pollutant removal rate, %; C 0 is the initial concentration of the polluted solution, mg / L; C t is the concentration of the polluted solution after adsorption by the adsorbent, mg / L; V is the volume of the polluted solution, L; m is the amount of adsorbent input, g.

[0044] like Figure 2 As shown, the removal rates R of CV and CR of AMK prepared in Example 1 are only 64.07% and 13.15%, and the adsorption amounts Q are 65.79 mg / g and 12.66 mg / g; the removal rates R of CV and CR of AGM prepared in Example 2 are 83.89% and 83.77%, and the adsorption amounts Q are 86.14 mg / g and 80.67 mg / g; the removal rates R of CR of XGM prepared in Example 4 and ZGM prepared in Example 3 can both reach 90%, and the adsorption amounts can both reach above 95 mg / g, while the removal rates R of CV are 84.55% and 99.03%, and the adsorption amounts Q are 86.825 mg / g and 101.724 mg / g, respectively.

[0045] like Figure 3 As shown, the removal rate R of Cd and Pb of AMK prepared in Example 1 is only 15.52% and 20.44%, and its adsorption amount Q is 31.04mg / g and 61.31mg / g. The removal rate R of Cd and Pb of AGM prepared in Example 2 is 31.32% and 96.53%, and its adsorption amount is 62.64mg / g and 289.59mg / g. The removal rate R of Pb of XGM prepared in Example 4 and ZGM prepared in Example 3 can reach more than 90%, and the adsorption amount Q can be close to 300mg / g, which are 273.53mg / g and 289.97mg / g respectively, while the removal rate of Cd is 68.365% and 93.37%, and the adsorption amount is 137.6mg / g and 186.74mg / g respectively.

[0046] In summary, after different types of biomass are doped with geopolymer microspheres, the adsorption effects are quite different. Among them, bagasse-slag-based composite microspheres ZGM and wheat straw-slag-based composite microspheres XGM have achieved significantly better technical effects on the treatment of CV, CR, Cd and Pb in dye solutions.

[0047] Comparative Example 1

[0048] On the basis of Example 1, without adding eucalyptus wood powder, metakaolin-based polymer microspheres were obtained, numbered MK.

[0049] Comparative Example 2

[0050] On the basis of Example 2, without adding eucalyptus wood powder, slag-based polymer microspheres were obtained, numbered GM.

[0051] Comparative Example 3

[0052] On the basis of Example 3, without adding slag, bagasse biochar was obtained, numbered BC.

[0053] Comparative Example 4

[0054] On the basis of Example 1, without adding metakaolin, eucalyptus charcoal was obtained, numbered AC.

[0055] Comparative Example 5

[0056] On the basis of Example 4, without adding slag, wheat straw charcoal was obtained, numbered XC.

[0057] The products prepared in Comparative Examples 1-5 were used as adsorbents to carry out adsorption experiments on dye crystal violet (CV), Congo red (CR) and heavy metals Cd and Pb. The results are shown in Table 1. Figure 4 , Figure 5 .

[0058] Depend on Figure 4 and Figure 2 contrast, Figure 5 and Figure 3 By comparison, it can be seen that the present invention prepares biomass-based geopolymer composite microspheres by compounding the biochar precursor with the geopolymer. Compared with the raw materials before balling, the adsorption effect of dyes CV, CR and heavy metals Cd and Pb is significantly improved.

[0059] Comparative Example 6

[0060] On the basis of Example 3, the filtered solid was not immersed in ammonia water, but directly placed in a porcelain boat and kept at 400°C for 4 hours in a tubular furnace under a nitrogen atmosphere. After cooling, the sample was washed with pure water until neutral and dried to obtain biomass-based geopolymer composite microspheres, numbered ZGM-1.

[0061] The method of the application example was used to perform adsorption experiments on simulated electroplating wastewater using AGM of Example 2, ZGM of Example 3, GM of Comparative Example 2, BC of Comparative Example 3, and ZGM-1 of Comparative Example 6 as adsorbents. The results are shown in Figure 6 and Figure 7 The simulated electroplating wastewater is prepared by mixing methylene blue (MB in the figure), copper nitrate (Cu in the figure), cobalt nitrate (Co in the figure) and nickel nitrate (Ni in the figure). The concentration of each pollutant in the prepared simulated electroplating wastewater is 50 mg / L.

[0062] like Figure 6 and Figure 7 As shown, when the wastewater composition is relatively complex, the adsorption effects of various adsorbents are different. The ZGM of Example 3 has a significantly better adsorption effect than the uncompounded GM and BC, while the AGM of Example 2 has a significantly lower effect than the ZGM of Example 3. It can be seen that not all types of biomass and geopolymer composites can achieve good technical effects by using the method of the present invention. The adsorption effect of ZGM-1 of Comparative Example 6 is significantly lower than that of ZGM of Example 3. Obviously, the present invention can effectively improve the adsorption effect of the product in a specific alkaline environment modification treatment.

[0063] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the definition of the claims.

Claims

1. A method for in-situ preparation of biomass-based geopolymer composite microspheres, characterized in that: The method comprises the following steps: uniformly mixing biomass powder, aluminosilicate raw material and alkaline activator to obtain slurry, dripping the slurry into 70-90°C silicone oil under stirring, continuously stirring for 10-15 minutes after the titration is completed, and then transferring the slurry into a 70-90°C oven for curing for 8-12 hours, and then performing vacuum filtration, soaking the obtained solid in ammonia water for 5-8 hours, and then keeping the temperature at 350-500°C for 3-5 hours in a nitrogen atmosphere, washing to neutrality after cooling, and drying to obtain biomass-based geopolymer composite microspheres.

2. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The concentration of the ammonia water is 5-10 mol / L.

3. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The biomass powder is any one or any combination of eucalyptus powder, bagasse powder and wheat straw powder.

4. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The aluminosilicate raw material is any one of metakaolin and slag or a combination of the two.

5. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The alkaline activator is 1.0 modulus water glass or 10-20 mol / L NaOH solution.

6. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The amount of the biomass powder added is 5-7g, the amount of the aluminosilicate raw material added is 25-30g, and the amount of the alkaline activator added is 25-50g.

7. The method for in-situ preparation of biomass-based geopolymer composite microspheres according to claim 1, characterized in that: The added amount of the biomass powder is 15-25% of the total weight of the biomass powder and the aluminosilicate raw material.

8. Use of the biomass-based geopolymer composite microspheres prepared by the method of claim 1 in industrial wastewater treatment.

9. The use according to claim 8, characterized in that: The industrial wastewater is printing and dyeing wastewater or electroplating wastewater.

10. The use according to claim 8, characterized in that: The biomass-based geopolymer composite microspheres are added into industrial wastewater for stirring or shaking. The concentration of the biomass-based geopolymer composite microspheres added into the industrial wastewater is 0.5-1.5 g / L.